Analisis Penerapan Akuntansi Manajemen Lingkungan Dan Inovasi Hijau Guna Mengevaluasi Kinerja Lingkungan: (Studi Pada Dinas Lingkungan Hidup Kabupaten Nganjuk Tahun 2022) - Gadis Ragil Krisistiya; Marhaendra Kusuma; Imarotus Suaidah (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
The aim of this research is to find out how environmental management accounting, green innovation and environmental performance are used by the Nganjuk Regency Environmental Service. Descriptive research with a qualitative approach was used. The data used in this research comes from interviews conducted in 2022, as well as data from the Nganjuk Regency Environmental Service. Descriptive analysis is used to analyze the data. describes the results of his findings based on the data collected.The results of this research indicate that the Nganjuk Regency Environmental Service has completed the treatment stages of implementing environmental management accounting for waste management costs and has evaluated the level of environmental performance well. In addition, they have implemented green innovation as a form of social responsibility to society and the environment, as seen in the presentation of waste management costs included in detailed financial reports. Furthermore, the more environmental performance evaluations carried out, the higher the level of community satisfaction. Conversely, the lower the level of environmental performance evaluation, the lower public satisfaction with the company.